CPR Guidance by an Emergency Physician via Video Call: A Simulation Study - Dong Keon Lee; Seung Min Park; Yu Jin Kim; Choung Ah Lee; Won Jung Jeong; Gi Woon Kim; Dong Hyuk Shin; Young Hwan Lee (Emergency Medicine International)
Background. In South Korea, the prehospital treatment of cardiac arrest is generally led by an emergency medical technician-paramedic (EMT-P), and defibrillation is delivered by the automatic external defibrillator (AED). This study aimed at examining the effects of direct medical guidance by an emergency physician through a video call that enabled prompt manual defibrillation. Methods. Two-hundred eighty-eight paramedics based in Gyeonggi Province were studied for four months, from July to November 2015. The participants were divided into 96 teams, and the teams were randomly divided into either a conventional group that was to use the AED or a video call guidance group which was to use the manual defibrillators, with 48 teams in each group. The time to first defibrillation, total hands-off time, and hands-off ratio were compared between the two groups. Results. The median value of the time to the first defibrillation was significantly shorter in the video call guidance group (56 s) than in the conventional group (73 s) (p<0.001). The median value of the total hands-off time was also significantly shorter (228 vs. 285.5 s) (p<0.001), and the hands-off ratio, defined as the proportion of hands-off time out of the total CPR time, was significantly shorter in the video call guidance group (0.32 vs. 0.41) (p<0.001). Conclusion. Physician-guided CPR with a video call enabled prompt manual defibrillation and significantly shortened the time required for first defibrillation, hands-off time, and hands-off ratio in simulated cases of prehospital cardiac arrest.